Pemanfaatan Daun Kelor bagi Pencegahan Stunting di Desa Surianeun Kabupaten Pandeglang - Trijani Moedjiherwati; Maria Octavianti; Ade Handriati; Bekti Handayani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2023)
Stunting prevention at the rural level must be carried out cross-sectorally and collaboratively. This is because there are still many obstacles and challenges in efforts to prevent stunting in rural areas. The main problem that is still faced by villagers in preventing stunting is the lack of knowledge for efforts to strengthen family nutrition and nutrition. In community service in Suriaenun Village, Pandeglang Regency which was held on 23th May 2023, assistance was provided in the use of Moringa leaves to prevent stunting. In this assistance, a variety of new knowledge has been given about efforts to utilize Moringa leaves for the creation of various processed food products. The mentoring participants were given tips and tricks for making Moringa leaf-based food products such as; Sponge Cake, Moringa Bakwan, Arem-Arem Cake, Stir-Fried Moringa and Moringa Leaf Soup. This activity has an impact on housewives because they already have the awareness to be able to use Moringa leaves for additional nutrition and family nutrition. This assistance can encourage housewives to be able to contribute to reducing stunting rates, starting from their own families. From the results of this activity it is known that the utilization of Moringa leaves through the creation of various food product variants can contribute to the prevention of stunting in Surianeun Village, Pandeglang Regency.